Approaches and Applications of Inductive Programming Third International Workshop, AAIP 2009, Edinburgh, UK, September 4, 2009. Revised Papers - Schmid, Ute.; Kitzelmann, Emanuel; Plasmeijer, Rinus; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes revised papers of the Third International Workshop on approaches and Applications of Inductive Programming, AAIP 2009, held in Edinburgh, UK, in September 2009. The 7 full papers included in this volume were carefully reviewed and selected. The book also contains two invited papers.
Invited Papers -- Deriving a Relationship from a Single Example -- Synthesis of Functions Using Generic Programming -- Regular Papers -- Inductive Programming: A Survey of Program Synthesis Techniques -- Incremental Learning in Inductive Programming -- Enumerating Well-Typed Terms Generically -- Generalisation Operators for Lists Embedded in a Metric Space -- Porting IgorII from Maude to Haskell -- Automated Method Induction: Functional Goes Object Oriented -- Recent Improvements of MagicHaskeller.
Keywords: Computer science; Software engineering; Logic design; Information systems; Artificial intelligence; Computer Science; Software Engineering; Artificial Intelligence (incl. Robotics).; Mathematical Logic and Formal Languages; Logics and Meanings of Programs; Information Systems Applications (incl.Internet).; Programming Techniques